2020
DOI: 10.3390/cancers12113212
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Papillary Thyroid Cancer Organoids for Radioactive Iodine Refractory Screening

Abstract: Patients with well-differentiated thyroid cancer, especially papillary thyroid cancer (PTC), are treated with surgical resection of the thyroid gland. This is followed by post-operative radioactive iodine (I131), resulting in total thyroid ablation. Unfortunately, about 15-33% of PTC patients are unable to take up I131, limiting further treatment options. The aim of our study was to develop a cancer organoid model with the potential for pre-treatment diagnosis of these I131-resistant patients. PTC tissue from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Organoids, a novel stem cell study model, have been introduced in the study of CSCs through the embedding of CSCs and other cancer-related cells in Matrigel or ECM-like biomaterials 6 . This model not only supports the CSC enrichment but also recapitulates the histopathology and cellular heterogeneity of tumors [7][8][9][10] . Additionally, unlike conventional study systems based on cancer cell lines, organoids can be generated from specimens of individual patients, thereby enabling the development of personalized therapeutic regimens 6 .…”
Section: Introductionsupporting
confidence: 68%
“…Organoids, a novel stem cell study model, have been introduced in the study of CSCs through the embedding of CSCs and other cancer-related cells in Matrigel or ECM-like biomaterials 6 . This model not only supports the CSC enrichment but also recapitulates the histopathology and cellular heterogeneity of tumors [7][8][9][10] . Additionally, unlike conventional study systems based on cancer cell lines, organoids can be generated from specimens of individual patients, thereby enabling the development of personalized therapeutic regimens 6 .…”
Section: Introductionsupporting
confidence: 68%
“…We have performed much in-depth investigation on the origin, pathology, and genetics of cancer in the past few decades, and we found that the knowledge gained from cell lines and PDX is not entirely consistent with the actual clinical situation. We are increasingly aware that cancer has different heterogeneity and , 2015), lung cancer (Dijkstra et al, 2020), liver cancer (Nuciforo et al, 2018), prostate cancer (Puca et al, 2018), breast cancer (Han et al, 2020), gastric cancer (Yan et al, 2018), pancreatic cancer (Seino et al, 2018), lymphatic cancer (Tian et al, 2015), esophageal cancer (Li et al, 2018), thyroid cancer (Sondorp et al, 2020), among others (Figure 2). These studies have shown that tumor organoids are highly similar to the original tumors in terms of genetic specificity, epigenetic characteristics, morphology, metabolism, proliferation rate, and metastatic potential.…”
Section: Organoids In Cancer Researchmentioning
confidence: 99%
“…The recently developed 3D culture technology has led to the development of new and more physiological organoids, thus creating new and more targeted therapies. In the more than 10 years since the emergence of organoids, scientists successfully cultivated all kinds of tumor organoids, such as bladder cancer ( Lee et al, 2018b ), colorectal cancer ( van de Wetering et al, 2015 ), lung cancer ( Dijkstra et al, 2020 ), liver cancer ( Nuciforo et al, 2018 ), prostate cancer ( Puca et al, 2018 ), breast cancer ( Han et al, 2020 ), gastric cancer ( Yan et al, 2018 ), pancreatic cancer ( Seino et al, 2018 ), lymphatic cancer ( Tian et al, 2015 ), esophageal cancer ( Li et al, 2018 ), thyroid cancer ( Sondorp et al, 2020 ), among others ( Figure 2 ). These studies have shown that tumor organoids are highly similar to the original tumors in terms of genetic specificity, epigenetic characteristics, morphology, metabolism, proliferation rate, and metastatic potential.…”
Section: Organoids As Disease Modelsmentioning
confidence: 99%
“…Recent research by Zupunski et al [ 3 ] found a correlation between subjects exposed to iodine-131 from Chernobyl’s fallout during childhood at age ≤18 years and thyroid cancer risk. This is of great concern, as iodine-131 is routinely administered as a radiopharmaceutical in nuclear medicine in the form of sodium iodide (NaI) for diagnosis and treatment of thyroid disease [ 4 ]. Approximately 80% of the administered iodine-131 is excreted in the urine [ 5 ]; therefore, it has potential to be discharged to sewage wastewater if not carefully controlled.…”
Section: Introductionmentioning
confidence: 99%